Association of Selinexor Dose Reductions With Clinical Outcomes in the BOSTON Study - Jagannath, Sundar; Delimpasi, Sosana; Grosicki, Sebastian; Van Domelen, Dane R; Bentur, Ohad S; Špička, Ivan; Dimopoulos, Meletios A (Clinical lymphoma, myeloma & leukemia, 2023)
BACKGROUND: Dose modifications in response to adverse events (AEs) can maintain tumor response and improve therapy tolerability. We conducted a post-hoc analysis of the efficacy and safety of reduced selinexor doses in the BOSTON trial (NCT03110562). PATIENTS AND METHODS: Efficacy, safety, and quality of life (QoL) in 195 patients with relapsed/refractory multiple myeloma randomized to once-weekly (QW) selinexor (100 mg), QW subcutaneous bortezomib (1.3 mg/m2), and twice-weekly dexamethasone (20 mg) were compared between patients with dose reductions and those without. RESULTS: In total, 126 patients (65%) had selinexor dose reductions (median dose 71.4 mg/wk). In patients with dose reductions versus those without median progression-free survival was 16.6 months (95% CI 12.9-not evaluable [NE]) versus 9.2 months [95% CI 6.8-15.5]), overall response rate was 81.7% (95% CI 73.9-88.1%) versus 66.7% (95% CI 54.3-77.6%), ≥very good partial response was (51.6% [95% CI 42.5-60.6%] vs. 31.9% [95% CI 21.2-44.2]), median duration of response was not reached (95% CI 13.8-NE) versus 12.0 months (95% CI 8.3-NE), and time to next treatment was 22.6 months (95% CI 14.6-NE) versus 10.5 months (95% CI 6.3-18.2). Mean best change from baseline on the EORTC QLQ-C30 Global Health Status/QoL scale was 10.0 ± 20.5 versus 4.0 ± 20.9. Duration-adjusted AE rates that were lower after selinexor dose reduction included thrombocytopenia (62.5% before vs. 47.6% after), nausea (31.6% vs. 7.3%), fatigue (28.1% vs. 9.9%), decreased appetite (21.5% vs. 6.4%), anemia (17.9% vs. 10.3%), and diarrhea (12.9% vs. 5.2%). CONCLUSION: Appropriate dose reductions in response to AEs of the 100 mg selinexor starting dose in the BOSTON study were associated with improved efficacy, reduced AE rates and improved QoL.
Keywords: vysazování léků; protokoly protinádorové kombinované chemoterapie; mnohočetný myelom; Multiple Myeloma; Humans; lidé; Quality of Life; dexamethason; kvalita života; Antineoplastic Combined Chemotherapy Protocols; Dexamethasone; Drug Tapering